Magnetic Molecularly Imprinted Polymers with Hydrophilic Shells for the Selective Enrichment and Detection of Rosmarinic Acid in Aqueous Extraction - Yanhui Wang; Linlin Yan; Guangyao Zheng (Plants)
Rosmarinic acid (RA) is a natural active compound widely found in many plants belonging to the family of Lamiaceae, Boraginaceae, and so on, which has various important bioactivities, including being anti-oxidative, anti-inflammatory, antiviral, etc. Herein, novel hydrophilic magnetic molecularly imprinted polymers (HMMIPs) with a regular core-shell structure were successfully developed using RA as a template molecule, acrylamide (AM) as a functional monomer, N-N ’methylenebisacrylamide (MBA) as a cross-linking agent, and water as the porogen. After a series of characterization and adsorption performance analyses, it was found that HMMIPs are hydrophilic with an adsorption capacity of 8.012 ± 0.54 mg/g, an imprinting factor of 3.64, and a selectivity coefficient of 2.63~2.91. Furthermore, the HMMIPs can be rapidly separated from other components under the influence of external magnetic fields. The HMMIPs were employed for the determination of RA present in the Perilla frutescens and Rosmarinus officinalis aqueous extract with recoveries of 88.2~107.3%. These results indicated that HMMIPs of RA have the benefits of straightforward operation, rapid adsorption, and high selectivity, rendering it an appropriate way for the expedient and selective isolation of RA in an intricate matrix.